Passenger Road Transport Trends in the Slovak Republic - Peter Faith (Communications - Scientific letters of the University of Zilina, 2008)
The article deals with the present trends in the passenger road transport in the Slovak Republic. It provides the characteristic of indicators of development phases of the passenger road transport trends. Existing increase of number of vehicles and individual road transport performances shall bring unfavourable impacts on environment on the one hand and on the other hand, it shall be the source of the state budget income.Permanent conflict between individual road transport and mass passenger transport makes all administrative authorities to follow impacts on the life of inhabitants in agglomerations with assumed higher concentration of inhabitants. Demand for passenger cars will be permanent and any decrease in the passenger road transport cannot be assumed. Therefore, it is necessary to show a permanent interest in this sphere of problems and deal with it on the highest possible level.